2020
DOI: 10.1016/j.measurement.2019.107194
|View full text |Cite
|
Sign up to set email alerts
|

Protocol to assess the quality of transmission lines within smart textile structures

Abstract: a b s t r a c tThe washability issue is always a challenge for electronic textiles in terms of application. It reduces their reliability, makes them not robust enough, and therefore not ready for the market. In this study, a novel protocol was designed to test the performance of conductive threads under wet situation in order to simulate the washing cycle. In this content, two commercially available silver-plated polyamide threads having the same thread count were used and washing results of each thread were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…For the Martindale test, a simple straight line was chosen (see Figure 4), which is in line with the literature (see Table 2 ). [ 39–45 ]…”
Section: Resultsmentioning
confidence: 99%
“…For the Martindale test, a simple straight line was chosen (see Figure 4), which is in line with the literature (see Table 2 ). [ 39–45 ]…”
Section: Resultsmentioning
confidence: 99%
“…The commercially available detergents contained particles that increased friction. The authors concluded that soaked abrasion is a suitable simulation for predicting the machine-washing lifetime of e-textiles [ 149 ].…”
Section: Accelerated Functional Ageingmentioning
confidence: 99%
“…So far, researchers have primarily focused on investigating the effects of adverse conditions on the fabrics, such as the effects of different types and classes of stitching [20], consecutive abrasion [21] or repeated washing cycles [15,21], as well as the effects of chemicals used as detergents or ironing agents [22]. However, very little light has been shed on how the conductive thread itself can handle power fed through it, and how that can affect it [23,24].…”
Section: Introductionmentioning
confidence: 99%